Foreword by the Editors - Journal, HEROS (Helsinki Romanian Studies Journal, 2025)
The third issue of HEROS Journal continues the journal’s commitment to exploring Romanian language, literature, and culture through a plurality of scholarly lenses and disciplinary approaches. The present volume brings together contributions that span historical inquiry, literary and cultural analysis, translation studies, linguistics, and language pedagogy, highlighting both diachronic depth and contemporary relevance within Romanian Studies and beyond. Several articles in this issue engage with historical and cultural foundations, offering new perspectives on formative moments and texts. From the cultural and morphological analysis of Johann Ignaz von Felbiger’s eighteenth-century bilingual educational work, to a socio-cultural examination of the emergence of modern Romanian theatre, the volume foregrounds the role of language, performance, and translation in shaping cultural identities. Other contributions address literary imaginaries and intertextual dialogues, such as the comparative exploration of mythological typologies in the fantasy worlds of Michael Ende and Răzvan Rădulescu, or the linguistic and translational analysis of verbal periphrases in Bacoviana by Mircea Cărtărescu. The issue also reflects the journal’s strong interest in multilingualism and language in use. Articles devoted to plurilingual approaches in teaching Romanian as a foreign language and to the translation of Romanian literary structures into other languages underscore the journal’s engagement with applied linguistics, pedagogy, and cross-cultural mediation. At the same time, the volume addresses pressing contemporary cultural debates, notably through a critical examination of the controversies surrounding manele in Romania, situated at the intersection of marginality, politics of taste, and cultural industries. The volume is further enriched by three book reviews that broaden its intellectual and thematic scope. These include a perceptive and inspiring review of a recent biography of Emil Cioran, offering a nuanced insight into the thinker’s life and intellectual legacy; a rigorous analysis of a volume devoted to Nadia Comăneci, read through the lens of surveillance and control during the Ceaușescu regime; and an informed assessment of a textbook for teaching Romanian as a foreign language, which highlights both its pedagogical coherence and its practical value. Together, these reviews contribute substantively to debates on intellectual history, memory and power, and contemporary language pedagogy. We would like to express our sincere gratitude to all the authors who have entrusted HEROS Journal with their work and whose contributions meet the high scholarly standards upheld by the journal. We are equally indebted to the peer reviewers, whose rigorous evaluations, careful attention to academic integrity, and constructive feedback have been essential in ensuring the quality, originality, and reliability of this issue. Their commitment plays a decisive role in maintaining the journal’s academic credibility and in strengthening the HEROS community as a space of excellence, responsibility, and scholarly dialogue. We hope that this third issue will inspire further research and foster meaningful conversations among scholars, students, and readers engaged with the intersections of language, literature, history, and culture. The Editors